Una lectura sobre la producción de alteraciones a los formatos escolares desde la política cotidiana de la escuela - Stevenazzi Alén, Felipe (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article proposes to investigate and analyze the alterations to school formats, from the construction of everyday politics, from the development experience of the teaching staff of a public school in Casavalle, Montevideo. The idea of change is developed as the need to produce an alter, which retrieves the "other" by placing it in the possibility, while teachers are restored as such. Barrios Casavalle characteristics are analyzed in relation to public policy and the current tensions between public and private policies. The school as a social encounter and erosion to a homogeneous space. Two levels of production of educational policies and the place of teachers in them are distinguished.